Representasi Perlawanan Intelektual Soe Hok Gie dalam Film Gie (2005) - Elsa Wulan Cahyanti (Forum for Social and Humanities Studies, 2026)
This study analyzes the representation of Soe Hok Gie's intellectual resistance in Riri Riza's film Gie. The film reconstructs Soe Hok Gie's intellectual journey and activism during the transition from the Old Order to the New Order. This study uses a qualitative approach, drawing on Stuart Hall's theory and semiotic analysis, to examine the film's sign system. The results show that the film portrays Gie as an intellectual activist who is critical of power, rejects dogmatism, and upholds the values of humanism and moral integrity. This representation is constructed through dialogue, visual composition, gestures, and a narrative flow that positions Gie as a symbol of intellectual resistance against practices of power deemed deviant. This study concludes that the film does not simply reproduce historical facts but also constructs certain meanings regarding student activism and the position of intellectuals in the public sphere. Thus, film shapes the contemporary generation's collective memory and interpretation of the figure of Soe Hok Gie and the dynamics of the 1960s student movement, while also emphasizing the role of intellectuals as the voice of public conscience. This research confirms that representation in film plays a strategic role in constructing new meanings of history, activism, and humanism during Indonesia's political transition. It can serve as a basis for strengthening the role of student intellectuals in observing and following the developments and dynamics of Indonesian politics.